Antioxidant Properties of Different Types of Torbangun Herbal Tea - Intan Cidarbulan Matita; Titri Siratantri Mastuti; Smita Maitri (Dept. of Chemical Engineering, Diponegoro University, 2020)
In this study, Torbangun leaves are processed into three different types varying in their oxidation degree, namely unoxidized, semioxidized and oxidized Torbangun leaves. Each type is then brewed into herbal tea and analyzed in terms of its total phenolic, total flavonoid and antioxidant activity. Unoxidized Torbangun herbal tea shows higher content of total phenolic (44.22 mg GAE/g) and total flavonoid (17.02 mg QE/g) compared to oxidized (24.66 mg GAE/g total phenolic content and 8.61 mg QE/g total flavonoid content) and semioxidized (33.83 mg GAE/g total phenolic content and 10.68 mg QE/g total flavonoid content) Torbangun herbal tea. In terms of the antioxidant activity, processing the Torbangun leaves into herbal tea tremendously decreased the antioxidant activity based on the IC50 value of 1400.89 ɥg/mL for unoxidized Torbangun herbal tea, 3211.71 ɥg/mL for semioxidized Torbangun herbal tea and 4504.78 ɥg/mL for oxidized Torbangun herbal tea. However, steam blanching used in the preparation of unoxidized Torbangun leaves is proven to increase the total phenolic and flavonoid content of raw or unprocessed Torbangun leaves from 39.02 to 44.22 mg GAE/g and an increase of total flavonoid from 10.32 to 17.02 mg QE/g.Keywords: antioxidant; flavonoid; herbal tea; phenolic; torbangun